Ensuring poverty : welfare reform in feminist perspective - Kornbluh, Felicia, 1966-; Mink, Gwendolyn, 1952- (University of Pennsylvania Press, 2019)
In Ensuring Poverty, Felicia Kornbluh and Gwendolyn Mink assess the gendered history of welfare reform, foregrounding arguments advanced by feminists for a welfare policy that would respect single mothers' rights while advancing their opportunities and assuring economic security for their families.